Deep roots delay flowering and relax the impact of floral traits and associated pollinators in steppe plants. - Rachda Berrached; Leila Kadik; Hocine Ait Mouheb; Andreas Prinzing (PLoS ONE, 2017)
Strong seasonality in abiotic harshness and pollinator availability shape the reproductive success of plants. Plant species can avoid or can tolerate harsh abiotic conditions and can attract different pollinators, but it remains unknown (i) which of these capacities is most important for flowering phenology, (ii) whether tolerance/avoidance of abiotic harshness reinforces or relaxes the phenological differentiation of species attracting different pollinators. We assembled possibly the first functional trait database for a North African steppe covering 104 species. We inferred avoidance of harshness (drought) from dormancy, i.e. annual life-span and seed size. We inferred tolerance or resistance to harshness from small specific leaf area, small stature, deep roots and high dry matter content. We inferred the type of pollinators attracted from floral colour, shape and depth. We found that avoidance traits did not affect flowering phenology, and among tolerance traits only deep roots had an effect by delaying flowering. Flower colour (red or purple), and occasionally flower depth, delayed flowering. Dish, gullet and flag shape accelerated flowering. Interactive effects however were at least as important, inversing the mentioned relationship between floral characters and flowering phenology. Specifically, among drought-tolerant deep-rooted species, flowering phenologies converged among floral types attracting different pollinators, without becoming less variable overall. Direct and interactive effects of root depth and floral traits explained at least 45% of the variance in flowering phenology. Also, conclusions on interactive effects were highly consistent with and without including information on family identity or outliers. Overall, roots and floral syndromes strongly control flowering phenology, while many other traits do not. Surprisingly, floral syndromes and the related pollinators appear to constrain phenology mainly in shallow-rooted, abiotically little tolerant species. Lack of abiotic tolerance might hence constrain accessible resources and thereby impose a stronger synchronization with biotic partners such as pollinators.